What Galvanic Vestibular Stimulation Actually Activates - Curthoys, Ian S.; MacDougall, Hamish G. (Frontiers in Neurology, 2012)
In a recent paper in Frontiers Cohen et al. (2012) asked “What does galvanic vestibular stimulation actually activate?” and concluded that galvanic vestibular stimulation (GVS) causes predominantly otolithic behavioural responses. In this Perspective paper we show that such a conclusion does not follow from the evidence. The evidence from neurophysiology is very clear: galvanic stimulation activates primary otolithic neurons as well as primary semicircular canal neurons (Kim and Curthoys, 2004). Irregular neurons are activated at lower currents. The answer to what behaviour is activated depends on what is measured and how it is measured, including not just technical details, such as the frame rate of video, but the exact experimental context in which the measurement took place (visual fixation vs total darkness). Both canal and otolith dependent responses are activated by GVS.